The Role of Mutual Legal Assistance in Obtaining Testimony From Foreign Witnesses - Setyardi, Untung (DAS Institute, 2025)
Research on Mutual Legal Assistance (MLA) has been widely conducted in various countries, but for Indonesia, this is a relatively new topic. This article aims to examine MLA from the perspective of law and social contract. The research focuses on methods that can be used to obtain testimony from foreign nationals who act as witnesses. In writing this article, the author employs a normative legal research method with a conceptual and legislative approach. The analytical technique used is literature study The research findings indicate that foreign nationals have the right to refuse to provide testimony in an Indonesian court without any legal consequences. This phenomenon results in a lack of critical evidence in criminal case investigations, specifically witness testimony.